Ventures of solidarity economy in focus 4 P's of the marketing of compound - Schulz, Jéferson Réus da Silva; Zajonz, Bruna Tadielo; Possani, Laura; Dörr, Andrea Cristina; Brum, Tônia Magali Moraes (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
The idea of fair, ethical and fair trade is related to a process of trade-oriented appreciation and recognition of the work and the expectations of producers and consumers. Practices that aim to encourage local economy, either within the production or consumption, require well-structured and elaborate marketing strategies. The objective of this paper is to discuss the potential of marketing as a way to promote and strengthen the solidarity economy enterprises through the 4 P's of marketing mix. The survey was conducted during the 21th and 10th FEICOOP Fair Latin American Solidarity Economy, characterized as a field survey. This study presents a sample of 140 forms applied in the public Monday during the 18th, 19th and 20th of July 2014 The results indicate that the public believes that the internet is the best place for dissemination of products, very good considering the idea of a website for dissemination. We conclude that the solidarity economy enterprises producer is primarily responsible for conducting the four elements that make up the marketing mix.